2013
DOI: 10.1074/jbc.m112.351064
|View full text |Cite
|
Sign up to set email alerts
|

Homotrimeric Macrophage Migration Inhibitory Factor (MIF) Drives Inflammatory Responses in the Corneal Epithelium by Promoting Caveolin-rich Platform Assembly in Response to Infection

Abstract: Background: MIF signals through the MAPK pathway to up-regulate proinflammatory cytokine synthesis. Results: Pseudomonas aeruginosa-induced infection up-regulates MIF homotrimer formation and stimulates assembly of caveolin-1-rich lipid raft, thereby promoting MAPK signaling. Conclusion:The homotrimeric form of MIF is the functionally active form of the molecule. Significance: The discovery of the functionally active oligomeric form of MIF allows preferential pharmaceutical targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Recent screening for intracellular pathways that stimulated NET release showed that activation of the MAPK p44/p45 pathway promoted NETosis over apoptosis [29]. Since we and others have reported that the endogenous cytokine MIF is rapidly released in response to infectious challenge and stimulates MAPK activation [17,30], the influence of MIF on NETosis was evaluated [31]. When MIF-deficient PMNs that were purified from MIF knock-out mice and were exposed to P. aeruginosa PAO1 , the resulting MAPK activation was sustained upon reconstitution with 100 ng rMIF as evident by the elevated phosphorylation state of p42//p44 at 30 min and 60 min post infection (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent screening for intracellular pathways that stimulated NET release showed that activation of the MAPK p44/p45 pathway promoted NETosis over apoptosis [29]. Since we and others have reported that the endogenous cytokine MIF is rapidly released in response to infectious challenge and stimulates MAPK activation [17,30], the influence of MIF on NETosis was evaluated [31]. When MIF-deficient PMNs that were purified from MIF knock-out mice and were exposed to P. aeruginosa PAO1 , the resulting MAPK activation was sustained upon reconstitution with 100 ng rMIF as evident by the elevated phosphorylation state of p42//p44 at 30 min and 60 min post infection (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…rMIF protein was produced in E. coli BL21 Star (DE3) cells (Invitrogen), after induction with 1mM IPTG for 3.5 hours as in [17]. Bacterial cells were pelleted by centrifugation in a Beckman Allegra 6R centrifuge (3,000 rpm, 15 min, ambient temperature).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these results demonstrate that both pathological adenovirus infection and adenoviral gene transfer utilize caveolae to infect the corneal epithelium. In addition to viral pathogens, infection of the corneal epithelium with Pseudomonas aeruginosa drives inflammatory signaling via macrophage migration inhibitory factor (MIF) by assembling caveolin-1-rich signaling platforms (Reidy et al, 2013). The Pseudomonas aeruginosa and MIF-dependent activation of the pro-inflammatory cytokine, interleukin-8, was suppressed by silencing of Cav-1.…”
Section: Caveolins/caveolae In Other Ocular Cellsmentioning
confidence: 99%
“…Although the crystal structure of MIF indicates that it is a trimer, other methods have been used to identify MIF monomers or dimers, in addition to the trimer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Sedimentation velocity and equilibrium ultracentrifugation data found MIF to be 97-98% trimeric species with a small amount of a large aggregate and an "incompetent monomer" not in equilibrium with the trimer (23).…”
mentioning
confidence: 99%